2010
DOI: 10.3354/meps08686
|View full text |Cite
|
Sign up to set email alerts
|

Using Gambusia affinis growth and condition to assess estuarine habitat quality: a comparison of indices

Abstract: Numerous indices have been used to estimate fish growth and condition; however, differences in sensitivity and reliability of the methods have hampered efforts to identify appropriate indicators for routine evaluation of habitat quality in the field. We compared common morphometric (length, weight, somatic growth, length-weight condition) and biochemical (RNA:DNA ratio, relative DNA content, energy density) growth indices on the same wild-caught mosquitofish Gambusia affinis to examine their usefulness as indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Examination of RNA:DNA to investigate growth rate is based on the premise that the amount of DNA in cells remains constant, while the amount of RNA increases with growth rate as more protein synthesis is required. This technique has been used successfully as a measure of relative growth in fishes (Buckley 1984, Folkvord et al 1996, Garcia et al 1998, Buckley et al 1999) and has been shown to typically integrate growth rates over a period of weeks (Johnson et al 2002, Piazza & La Peyre 2010.White grunts were collected from artificial reefs using mesh wire traps with mesh sizes of 1 and 2 cm in April 2010. Traps were deployed in the benthos surrounding the artificial reefs and were allowed to soak for 2 to 14 h before being retrieved.…”
mentioning
confidence: 99%
“…Examination of RNA:DNA to investigate growth rate is based on the premise that the amount of DNA in cells remains constant, while the amount of RNA increases with growth rate as more protein synthesis is required. This technique has been used successfully as a measure of relative growth in fishes (Buckley 1984, Folkvord et al 1996, Garcia et al 1998, Buckley et al 1999) and has been shown to typically integrate growth rates over a period of weeks (Johnson et al 2002, Piazza & La Peyre 2010.White grunts were collected from artificial reefs using mesh wire traps with mesh sizes of 1 and 2 cm in April 2010. Traps were deployed in the benthos surrounding the artificial reefs and were allowed to soak for 2 to 14 h before being retrieved.…”
mentioning
confidence: 99%
“…Size of commercial species is of particular importance for fisheries, since larger specimens are usually more valuable. Body condition measures in fish are commonly used as indicators of ecosystem health in transitional waters, being employed to evaluate productivity and anthropogenic pressures among habitats (Amara et al 2007;Piazza and La Peyre 2010;Cavraro et al 2019). This work emphasises that fish individual weight in transitional waters can be influenced by morphology and seascape structure, these being potential drivers of fish individual health.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, other studies in this system demonstrate that these riverine flood pulses deliver a significant amount of basal resources (140 µM of total N, 5 µM total P) at a level that is directly comparable to other allochthonous resource pulses in aquatic habitats (migratory salmon, [8]; migratory waterfowl, [44]; cicada carcasses, [9]) and that these nutrients are rapidly assimilated in the upper estuary [24]. Studies in this estuary also show that riverine nutrients propagate into the resident nekton consumers [25][26], [28]–[29] supporting the bottom-up control concept. However, we did not quantify the actual transfer of this subsidy to the higher-order consumers (i.e., predation).…”
Section: Discussionmentioning
confidence: 99%
“…These resources are readily assimilated by secondary consumers [12] , [25] – [28] and may be responsible for increased nekton growth, changes in community structure, and trophic diversity [28] – [31] . Riverine pulses are particularly important for recruitment of resident nekton consumers that key into these flood events for spawning and rapid growth [21] , [29] [30] , [32] .…”
Section: Introductionmentioning
confidence: 99%